(untitled) (Ameghiniana, 2014)
An almost complete skull of a carnosaur from the Allen Formation (Maasqichtian of Rio Negro Province) is described as the holotype of A belisaurus comahuensis. It is a high skull with a broad interorbital roof, a huge preorbital opening, squamosal nearly horizontal with the quadratojugal process ventraly directed, very wide infratemporal fenestra, very long quadrate, orbital opening large with almost closed orbita. The differences with Tyrannosauridae and other Cretaceous carnosaurs families appear so significant as to propose a new family, Abelisauridae, likely of gondwanic distribution. ·